[P203] WEPL-corrected margins for moving targets in carbon-ion gated treatments: Preliminary results. (August 2018) - Meschini, Giorgia; Vai, Alessandro; Riboldi, Marco; Pella, Andrea; Vitolo, Viviana; Caivano, Donatella; Ciocca, Mario; Baroni, Guido; Molinelli, Silvia
Abstract : Purpose: To evaluate intra- and inter-fractional robustness of carbon-ion treatment plans based on water-equivalent path length (WEPL) corrected ITV margins for moving targets irradiated with gated pencil-beam scanning. Methods: As a preliminary study, three patients with thoraco-abdominal targets were considered. Clinical plans were optimized with an Intensity Modulated Particle Therapy (IMPT) algorithm and the use of case-specific avoidance structures to prevent radiation pathways on regions subject to intra- and inter-fractional variations. Plans were optimized on the end-exhale CT of a 4DCT dataset using 2 fields and tested for consistency within the gating window by recalculation on the 30%-exhale and 30%-inhale CTs. Single Field Uniform Dose (SFUD) plans were optimized on beam-specific WEPL-corrected ITV ( ITV WEPL ), which comprised the envelope of water-equivalent target positions within the ideal gating window. Differently from clinical plans, avoidance structures were not used in this approach. Clinical plans were taken as reference for comparison. Dose recalculations on the planning 4DCT and on synthetic 4DCT simulating irregular breathing allowed to evaluate intra-fractional robustness of the two approaches, whereas inter-fractional robustness was estimated on re-evaluation CTs (one per patient). Differences in the conformity index CI = V 95 % / V target, target coverage D 95 % and homogeneity index HI = ( D 2 %  −  D 98 % )/ D 50 % between the end-exhale plan and the recalculated dose distributions were computed. Doses to the involved organs at risk (OARs) were evaluated as well. Results: The CI presented slightly higher median intra-/inter-fractional variations and absolute values in the ITV WEPL approach (13%–1.47) with respect to reference plans (6%–1.36). D 95 % and HI showed lower median intra-fractional variations for the ITV WEPL approach (0.1% and 35%) compared to reference plans (3.4% and 46%). In case of inter-fractional changes, the use of ITV WEPL led to higher median variations but comparable absolute values for D 95 % (3.8% vs 2.2%) and for HI (144% vs 20%, absolute median values: 0.11 vs 0.14). The two methods performed similarly in OARs. Conclusions: The use of WEPL-corrected ITV permits adequate tumor coverage even in presence of irregular breathing motion, for the small analyzed sample. Although uncertainties due only to intra-fractional organ motion were considered in the ITV WEPL approach, comparable inter-fractional robustness was found among the two strategies.